1988
DOI: 10.1063/1.341240
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of gold with gallium arsenide

Abstract: Gold and gold-based alloys, commonly used as solar-cell contact materials, are known to react readily with gallium arsenide. Experiments designed to identify the mechanisms involved in these GaAs-metal interactions have yielded several interesting results. It is shown that the reaction of GaAs with gold takes place via a dissociative diffusion process. It is shown further that the GaAs-metal reaction rate is controlled to a very great extent by the condition of the free surface of the contact metal, an interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…This concerns the formation of new material phases. In several earlier studies [9,19,12,14,[16][17][18] these phases have been identified as AuGa alloys and phases close to Ni 2 GeAs. These phases penetrate only tens of nm below the original wafer surface for typical annealing conditions [9,14].…”
Section: Summary Of Annealing Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…This concerns the formation of new material phases. In several earlier studies [9,19,12,14,[16][17][18] these phases have been identified as AuGa alloys and phases close to Ni 2 GeAs. These phases penetrate only tens of nm below the original wafer surface for typical annealing conditions [9,14].…”
Section: Summary Of Annealing Mechanismmentioning
confidence: 99%
“…Various authors have suggested that the increasing contact resistance that is associated with over annealing may be due to a large number of vacancies just below the metal-rich phases near the surface [19,14,24] (but others suggested it was due to excessive in-diffusion of Ni [5,14]). These mainly result from out-diffusion of Ga into the Au-rich grains (which indeed results in a very stable AuGa phase near the original wafer surface [5,16,17]). These vacancies occur in particular when there is no (longer) Ge diffusion into these vacancies.…”
Section: Summary Of Annealing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallium defects in the Au are expected as Au and GaAs are thought to react 31 through a dissociative diffusion mechanism 32,33 in which Ga enters the Au as an interstitial. These Ga i atoms are very mobile 31,32 but have a very low solubility limit.…”
Section: Discussionmentioning
confidence: 99%
“…However, when a Ga i encounters a gold vacancy V Au , the vacancy is annihilated and a substitutional Ga s is formed. 32,35 Therefore, the diffusion rate is approximated as equal to D Au . As the Ga i are removed, more are allowed to enter from the GaAs.…”
Section: Discussionmentioning
confidence: 99%